The Effect of Micellization on the Epr Spectra and Reactivity of 2,2,4,4-Tetramethylpiperidinoxyl (Tempo) Radicals - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C (John Wiley and Sons Ltd, 2016)
A series of 4-alkanoyloxy-2,2,6,6-tetramethylpiperidinoxyl radicals was prepared, and their reactivity in water vis-à-vis antioxidant Trolox was compared. Spectral (electron paramagnetic resonance) and dynamic-light-scattering measurements suggested the formation of micelles for the more hydrophobic members of the series. The observed increase in reactivity for the micelle-forming radicals reflected the increased local concentration of the radical fragment on the micellar interface. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd.